2003
DOI: 10.1128/iai.71.9.5169-5177.2003
|View full text |Cite
|
Sign up to set email alerts
|

Insertional Inactivation ofpacandrmlBGenes Reduces the Release of Tumor Necrosis Factor Alpha, Interleukin-6, and Interleukin-8 Induced byStreptococcus mutansin Monocytic, Dental Pulp, and Periodontal Ligament Cells

Abstract: Streptococcus mutans possesses different cell wall molecules, such as protein of the I/II family, the serotype f polysaccharide rhamnose glucose polymer (RGP), and lipoteichoic acid (LTA), which act as adhesins and modulins, allowing S. mutans to colonize teeth and cause dental caries and pulpitis. We tested several isogenic mutants of S. mutans defective in protein I/II and/or RGP, as well as purified modulins such as protein I/II, RGP, and LTA, for their binding and activation abilities on monocytic, dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 48 publications
0
45
0
Order By: Relevance
“…However, with the exception of their LPS or LPS-like materials, none of them has been analyzed at the molecular level. In addition, there are only limited data on induction of IL-8 expression in PDL cells as a result of bacterial factors (12,17), although IL-1␤ is known to be a stimulus for IL-8 expression in PDL cells (1,26). In the present study, we showed that the surface proteins of oral spirochetes cause IL-8 expression in PDL cells.…”
Section: Vol 73 2005 Induction Of Icam-1 and Cytokines By Spirochetmentioning
confidence: 48%
“…However, with the exception of their LPS or LPS-like materials, none of them has been analyzed at the molecular level. In addition, there are only limited data on induction of IL-8 expression in PDL cells as a result of bacterial factors (12,17), although IL-1␤ is known to be a stimulus for IL-8 expression in PDL cells (1,26). In the present study, we showed that the surface proteins of oral spirochetes cause IL-8 expression in PDL cells.…”
Section: Vol 73 2005 Induction Of Icam-1 and Cytokines By Spirochetmentioning
confidence: 48%
“…Since Hsa and AgI/II polypeptides have been shown to interact with receptors on erythrocytes and monocytes (13,53), we investigated the effects of inactivating Hsa or AgI/II polypeptide genes on adhesion of S. gordonii to HEp-2 human epithelial cells. At a multiplicity of infection of 100:1 (ratio of streptococci to HEp-2 cells) about 27% of the input wild-type DL1 bacteria adhered to the epithelial cell monolayers (Fig.…”
Section: Vol 73 2005mentioning
confidence: 99%
“…Fibronectin, collagen, laminin, and elastin are considered the most common components of ECM (63) and can serve as receptors for bacteria during infection. Some S. mutans surface structures, such as the P1 protein (also known as antigen I/II or SpaP), the wall-anchored protein A (WapA), the biofilm regulatory protein A (BrpA), the autolysin AtlA, the glucosyltransferases (GtfB, GtfC, and GtfD), and the serotype-specific RGP, have been implicated in the pathogenesis of IE by promoting adherence to endothelial tissues and triggering inflammatory responses (17,55,61). More recently, a new surface protein with collagen-and laminin-binding activity, Cnm, which has an uneven distribution among the different serotypes of S. mutans, was identified (47,51,52).…”
mentioning
confidence: 99%
“…In some cases, binding to the extracellular matrix (ECM) is the first step in the invasion of host cells (17,58). The ECM is a macromolecular structure that becomes exposed when tissue integrity is damaged by lesions or traumas (63).…”
mentioning
confidence: 99%